2016
DOI: 10.1177/0954407016656543
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the stability of a turbocharger centrifugal compressor by tip leakage control

Abstract: The occurrence of surge or stall in a centrifugal compressor and the role of the tip clearance flow in the instability in the centrifugal compressor are investigated in this study. A computational method is used to study the flow field in the centrifugal compressor in order to gain a better understanding of the surge or stall mechanism. It is found that, near surge or stall conditions, the tip leakage flow at the leading edge deflects more upstream; as the deflection increases, a more severe spillage occurs wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…For this purpose, the simulation results should be compared with the experimental results. As the current work is done and simulated by the same CFD software EURANUS (NUMECA), the same turbulence model (S-A) and the same boundary conditions as the work done by Mirzaee et al [33], the validation reported in their research work is used for validating the numerical simulation in this study. They compared the overall performance of the CFD results and experimental results.…”
Section: Validation With Experimental Datamentioning
confidence: 99%
“…For this purpose, the simulation results should be compared with the experimental results. As the current work is done and simulated by the same CFD software EURANUS (NUMECA), the same turbulence model (S-A) and the same boundary conditions as the work done by Mirzaee et al [33], the validation reported in their research work is used for validating the numerical simulation in this study. They compared the overall performance of the CFD results and experimental results.…”
Section: Validation With Experimental Datamentioning
confidence: 99%
“…This study demonstrated the advantage of the suction flow control method by showing both surge margin and pressure ratio improvements. Mirzaee et al [14] studied air injection method on a centrifugal compressor to increase stability. They examined different injection parameters ahead of the leading edge of the impeller and reported that this method was able to reduce the leakage flow from the propeller.…”
Section: Introductionmentioning
confidence: 99%
“…The tip clearance leakage flow (TLF) is associated with the compressor pressure ratio, 20,21 efficiency, 22,23 and stability. [24][25][26] Therefore, the circumferential difference of the TLF has attracted widespread attention. The angle a between the tip clearance leakage vortex trajectory and the axial direction is used to measure the degree of circumferential deflection of the TLF.…”
Section: Introductionmentioning
confidence: 99%